Variational Iteration Method in the Fractional Burgers Equation - Plata, A. R. Gómez; Oliveira, E. Capelas de (Journal of Applied Nonlinear Dynamics, 2026)
The variational iteration method (VIM) is a analysis tool efficient for approximate non-linear fractional differential equations. Recently differents investigators are used this method in your works and we study the Lagrange multipliers of the variational iteration method for the time fractional Burgers equation and apply those in differents particular cases. In this conference we present approximations of the solutions for a particular case of the time fractional Burgers equation (BF), with the use of the variational iteration method, the Caputo derivate for 0